PENGARUH LATIHAN SMALL SIDED GAME TERHADAP KETEPATAN PADA MAHASISWA PEMBINAAN PRESTASI SEPAK BOLA - Suyatmin Suyatmin; Kurnia Dyah Anggorowati; Eko Rudiansyah (Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi (Penjaskesrek), 2023)
Abstract: The background of the problem of this research is that there are still many students who are not precise in carrying out passing, the passing carried out by students has not been directed towards the specified target. This study aims to determine the effect of small-sided games training on the passing accuracy of STKIP Melawi physical education students who participate in soccer achievement coaching. The subjects of this study were students of the Physical Education Study Program who took part in football achievement coaching, while the sample in this study consisted of 20 students, taken using purposive sampling. The instrument in this study used the underpass accuracy test from Subagyo Irianto with a validity coefficient of 0.812 and a reliability coefficient of 0.879. The data analysis technique uses the t-test through the prerequisite tests for normality and homogeneity. The results showed that there was an effect of small-sided games training on the passing accuracy of STKIP Malawi Physical Education students who took part in football achievement coaching. This is evidenced by the significance value calculated in the t-test for the pre-test and post-test groups of 0.000, which is less than 0.05 (Sig 0.05). Keywords: small-sided games, passing accuracy.Abstrak: Latar belakang dari permasalahan penelitian ini adalah masih banyak mahasiswa kurang tepat dalam melakukan passing, passing yang dilakukan mahasiswa belum  terarah dengan sasaran yang ditentukan. Penelitian ini bertujuan untuk mengetahui pengaruh latihan small sided games terhadap ketepatan passing mahasiswa Pendidikan jasmani STKIP Melawi yang mengikuti pembinaan prestasi sepak bola. Subjek dari penelitian ini adalah mahasiswa prodi Pendidikan jasmani yang mengikuti pembinaan prestasi sepak bola, sedangkan sampel dalam penelitian ini berjumlah 20 Mahasisiwa, diambil dengan cara purposive sampling. Instrumen dalam penelitian ini menggunakan tes ketepatan passing bawah dari Subagyo Irianto dengan koefisien validitas 0,812 dan koefisien reliabilitas 0,879. Teknik analisis data menggunakan uji t melalui uji prasyarat normalitas dan homogenitas. Hasil penelitian menunjukkan terdapat pengaruh latihan small sided games terhadap ketepatan passing mahasiswa Pendidikan jasmani STKIP Melawi yang mengikuti pembinaan prestasi sepak bola. Hal ini dibuktikan dengan nilai signifikansi hitung pada uji t kelompok pre test dan post test sebesar 0,000 lebih kecil dari 0,05 (Sig 0,05).Kata Kunci: small-sided games, ketepatan passing.